A Novel Low Reynolds Number Airfoil Design for Small Horizontal Axis Wind Turbines. Issue 4 (August 2014) - Shah, Haseeb; Mathew, Sathyajith; Lim, Chee Ming
In order to improve the performance of small horizontal axis wind turbines at low wind speed, this study designs a novel airfoil section with an optimum transition ramp through multipoint inverse design method. A viscous analysis code is used to close the design loop. Further, Shear stress transport-transition model in ANSYS-Fluent is employed with modified constants to analyze the flow and aerodynamic performance of the airfoil at Reynolds numbers 60 000, 100 000, 200 000, 300 000 and 500 000. Next we consider the designing of a 2m rotor from the new airfoil section using an evolutionary algorithm for optimization. The power coefficient and self starting of a small 2m wind turbine is improved significantly with the chosen generator resistive torque of 0.5Nm, the new airfoil section and the optimization technique for finding the optimal values of the parameters.